Singular integral inequalities with several nonlinearities and integral equations with singular kernels - Medveď, M. (Нелінійні коливання, 2008)
We deal with an integral inequality with a power nonlinearity in its left-hand side, with n nonlinearities in
its right-hand side, and weakly singular kernels. The obtained result is an extention of the Bihari, Henry,
Pachpatte and Pinto inequalities and results obtained by the author. Using these results we prove sufficient
conditions for existence of global solutions of some nonlinear Volterra integral equations with singular
kernels and n nonlinearities. Розглянуто iнтегральнi нерiвностi зi степеневою нелiнiйнiстю в лiвiй частинi, n нелiнiйностями у правiй частинi та слабкосингулярними ядрами. Отриманий результат є узагальненням
нерiвностей, одержаних Бiхарi, Генрi, Пачпатт та Пiнто, а також результатiв автора. На
основi цих результатiв встановлено достатнi умови iснування глобальних розв’язкiв деяких
нелiнiйних iнтегральних рiвнянь Вольтерри з сингулярними ядрами та n нелiнiйностями.